2020
DOI: 10.1007/s11102-020-01034-2
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary metastases: presentation and outcomes from a pituitary center over the last decade

Abstract: Purpose Highlight and characterize manifestations, diagnostic/management approaches and outcomes in a contemporary cohort of patients with pituitary metastases (PM) from a large European pituitary center-over 10 years. Methods Retrospective review of PM cases between 1/2009 and 12/2018. Clinical, laboratory, imaging data at PM detection and during follow-up were analysed. Results 18 cases were identified (14 females; median age at diagnosis 61.5 years). Most common primary malignancies were lung (39%) and brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
28
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 19 publications
(76 reference statements)
4
28
1
2
Order By: Relevance
“…The frequency of such presentation varies in the literature, possibly influenced by the time of publication (6). Interestingly, different series found that most cases of PM preceding the diagnosis of malignancy originated from lung cancers, as the case we report (3,6,7,8).…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations
“…The frequency of such presentation varies in the literature, possibly influenced by the time of publication (6). Interestingly, different series found that most cases of PM preceding the diagnosis of malignancy originated from lung cancers, as the case we report (3,6,7,8).…”
Section: Discussionmentioning
confidence: 47%
“…PM has been associated with end-stage disease, and therefore with a poor prognosis (1). However, survival time from PM detection appears longer than previously reported, possibly reflecting improvements in the management of advanced malignancy (3,5,6). The management of PM depends on the symptoms and extent of the lesion, but also the stage of the primary malignancy and other comorbidities.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Diabetes insipidus and visual symptoms are prominent symptoms that point to pituitary metastasis in patients with a known malignancy [ 8 ]. Many of these symptoms are due to the compression and/or invasion of surrounding structures such as cranial nerves [ 9 ]. Our patient developed a headache, which was his presenting symptom.…”
Section: Discussionmentioning
confidence: 99%